Pengelolaan Dan Penginputan Data Sumber Daya Air Sebagai Pendukung Program Satu Data Di Dinas Pengelolaan Sumber Daya Air Provinsi Sumatera Selatan - Ririn Ulandari; Gusmelia Testiana (Jurnal Ilmu Komputer dan Informatika | E-ISSN : 3063-9026, 2026)
The management and input of water resources data play a crucial role in supporting the implementation of the One Data Program, which aims to create accurate, integrated, and accountable data across government institutions. This study discusses the process of managing and entering water resources data at the Water Resources Management Office of South Sumatra Province. The methods used include observation, documentation, and direct involvement in data processing activities within the One Data system. The results show that proper data management and systematic data entry can improve data quality, accessibility, and consistency, thereby supporting better decision-making and policy formulation. However, several challenges were identified, such as data inconsistencies, limited human resources, and technical constraints in system utilization. Therefore, improvements in coordination, training, and system optimization are necessary to enhance the effectiveness of the One Data Program implementation.